An acute abdomen packed full of surprises: a case report - Ramji, Ashwath Narayan (International Surgery Journal, 2019)
“Acute abdomen” is a clinical diagnosis which defines the emergent nature of the condition, rather than the condition itself, and the true diagnosis is often only made after laparotomy or laparoscopy. On occasion, the final diagnosis is drastically different from what was clinically suspected. Diseases such as diverticulosis can have multiple possible pathological outcomes as a consequence of their inflammatory nature, such as stricture formation, adhesions, acute diverticulitis, diverticular abscess, perforation and even malignant transformation. Usually one of these complications will be the presenting factor with rarely another complication discovered during management, which may or may not have been symptomatic. Extremely rarely, will multiple pathological outcomes of a condition be present together. Here we report the case of a male patient who underwent laparotomy for a suspected hollow viscus perforation, with the resulting findings a bewildering surprise.